The nutritional impact of diversified cropping systems: comparing diversified cropping patterns in Dinajpur, Bangladesh - Md. Arifur Rahaman; Alanuzzaman Kurishi, A.S.M.; Cheesman, Stephanie; Hossain, Md. Khaled; Parupalli, V.L. Bharathi; Md Nuruzzaman Haque; Hossain, Shakhawat; Ferdous, Zannatul; Huda, Md. Shamsul; Gathala, Mahesh Kumar; Krupnik, TimothyJ. (TAFSSA, 2024)
This trial brief summarizes the results of nutritional yields from diversified cropping systems after one full cropping cycle. The area for the trial was selected based on factors such as food security and nutrition adequacy, environmental degradation, and climate challenges, which are critical for achieving TAFSSA’s goals. Therefore, this research trial aims to highlight the importance of crop diversification and identify strategies to increase the cultivation of nutritionally rich crops that provide essential macro- and micronutrients.